The Analisis Penerapan Permendagri Nomor 20 Tahun 2018 Tentang Pengelolaan Keuangan Desa - Anisya Lestari Icha; Hasna Mudiarti; Heni Risnawati; Liana Nurdayanti (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the implementation of the Minister of Home Affairs Regulation No. 20 of 2018 concerning village financial management, with a case study in Jatimekar Village, Jatiluhur District, Purwakarta Regency. The regulation was issued as a guideline to enhance transparency, accountability, and efficiency in managing village funds, which are vital for supporting rural development and community welfare. The research employs a qualitative approach using interviews and documentation techniques to gather relevant data on the application of financial management principles in Jatimekar Village. Findings indicate that the village government has implemented the regulation in accordance with established procedures, covering stages such as planning, implementation, administration, reporting, and accountability of village finances. The use of the village financial system application (SISKEUDes) has been instrumental in ensuring systematic management, accurate documentation, and efficient reporting of financial activities. Moreover, the adoption of this application supports compliance with regulatory standards while also strengthening transparency for stakeholders, particularly the community. Although challenges such as limited human resource capacity and the need for continuous technical training remain, the overall implementation demonstrates alignment with the regulatory framework. This research highlights the importance of strengthening institutional capacity and digital literacy to maximize the effectiveness of SISKEUDes and ensure sustainable governance practices. Therefore, the study concludes that the application of the Minister of Home Affairs Regulation No. 20 of 2018 in Jatimekar Village reflects a positive step toward improving accountability, transparency, and efficiency in village financial management, which may serve as a model for other villages in Indonesia.